Efficient Electrotransformation of Bacillus thuringiensis for Gene Manipulation and Expression. Issue 11 (9th November 2022) - Zegeye, Ephrem Debebe; Aspholm, Marina
Abstract: Genetic manipulation of Bacillus spp., such as B. thuringiensis and B. cereus, is laborious and time consuming due to challenges in transformation of the plasmid DNA construct. Larger shuttle plasmids, such as pMAD, that are commonly used in markerless gene replacement are particularly difficult to transform into Bacillus spp. Here, we present robust protocols that work efficiently for the transformation of both small and large plasmid constructs into B. thuringiensis . Our protocols involve preparation of efficient electrocompetent Bacillus cells by cultivating the cells in the presence of a cell wall–weakening agent, followed by washing the cells with optimized solutions. The protocols further highlight the importance of using unmethylated plasmid DNA for the efficient transformation of B. thuringiensis . © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of electrocompetent B. thuringiensis Basic Protocol 2 : Transformation of B. thuringiensis